Modern pedagogic technologies in training sessions of HEIs (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Modern pedagogical technologies used in classes in higher education institutions include the use of information and communication technologies, interactive teaching methods, problem-based learning, project activities